Literature Review: Red Dragon Fruit (Hylocereus costaricensis) as an Alternative Stain to Hematoxylin-Eosin in Histology Preparation Making - Asyah, Siti; Nailufar, Yuyun; Astuti, Tri Dyah (Menara Journal of Health Science, 2024)
Dragon fruit is a tropical fruit of the cactus type, which has several types, one of which is red dragon fruit (Hylocereus costaricensis). Red dragon fruit is one type of fruit that has bioactive components such as flavonoids, phenolics, betasianin, and anthocyanins. One of the dominant bioactive components in red dragon fruit is anthocyanin. Anthocyanins are a group of red to blue pigments that are distributed in plants. Anthocyanins in the skin of red dragon fruit are higher than in the fruit flesh so that it can be used as an alternative stain in histology staining. Histology is the knowledge or science of tissues, plants, and animals. One of the stages of making histological preparations is staining. Staining is a process of staining tissues that aims to observe using a microscope and distinguish parts of the tissue to be observed, such as cell nuclei, cytoplasm, and others. One of the stains used is Hematoxylin-Eosin. Hematoxylin-Eosin is a general tissue stain to see tissue morphology. Hematoxylin-Eosin consists of two types of colours, namely Hematoxylin and Eosin. Hematoxylin as a cell nucleus binding dye that is stained blue and weakly bound while eosin as a dye that gives some shades to the tissue and its shades give a red colour to the tissue. The use of eosin is carcinogenic when used in the long term continuously so that it can cause cancer and the remaining waste can damage the environment. Alternative dyes are needed to reduce the impact of eosin use, one of which is by staining red dragon fruit. This study aims to look at the potential of colour uptake in alternative staining of red dragon fruit and staining images on histological smears. The method used in this research is the literature review method. This literature selection on several databases including Google Sholer, PubMed, and Semantic Scholer. There were 5 journals used as literature sources and analysed descriptively qualitatively. The results of this study were obtained in journals 1, 2, 3, and 5 in each tissue sample with good results because the concentration used was small so as to get good results while in the 4th journal obtained very good results because the concentration used was getting bigger so as to get very good results. The conclusion of this study is that each tissue sample produces good and excellent staining.